The Development of Applications on Smartphones for the 6Ts Technique to Enhance the Reading Music Notation Ability of Mathayomsuksa 4 Students - Srichan, Natthakarn; Sean Buakanok, Fisik; Promkhun, Pramote (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The development of applications on smartphones for the 6Ts Technique to enhance the reading music notation ability of Mathayomsuksa 4 students. The objectives of this study are 1) To create and find the efficiency of applications on smartphones for the 6Ts technique to increase the enhanced reading music notation ability of Mathayomsuksa 4 students to be effective according to the 80/80 2) To compare the enhanced reading music notation ability of Mathayomsuksa 4 students who study with applications on smartphones using the 6Ts technique. The sample group was students in Bunyawat Witthayalai School, Lampang Province at the Mathayomsuksa 4 students, Room 8 and Room 9, where they study the subject of Art Education (Music) in the 2nd semester of the academic year 2023 with 60 students. Methodology: This research uses Experimental Research. using the Randomized Control Group Posttest Only Design model. The tools were 1) Lesson plans on reading music notation 2) Applications on smartphones 3) Evaluation test during learning 4) Evaluation test after learning 5) Evaluation test enhances reading music notation ability. Statistics used: Mean, Percentage, Standard Deviation, t-test independent test. Results: 1) The creating and finding of the efficiency of applications on smartphones for the 6Ts technique enhances the reading music notation ability of Mathayomsuksa 4 students. The quality is at the highest level, equal to 4.55, and has One-to-one performance, small group, and field equal to 86.67/88.89, 81.11/86.67, and 80.83/85.22 respectively, according to the specified criteria. 2) The comparison of the enhancement to reading music notation ability between the experimental group and the control group, it was found that the experimental group had a better enhancement to reading music notation ability than the control group. with a statistical significance level of 0.05 Conclusion: The group Smartphone applications for 6Ts techniques are of high quality and efficiency. Meet the criteria and increase students enhance to reading music notation ability.